2013
DOI: 10.1021/jm3012036
|View full text |Cite
|
Sign up to set email alerts
|

Beyond H2S and NO Interplay: Hydrogen Sulfide and Nitroprusside React Directly to Give Nitroxyl (HNO). A New Pharmacological Source of HNO

Abstract: Hydrogen sulfide (H2S) has been increasingly recognized as an important signaling molecule that regulates both blood pressure and neuronal activity. Attention has been drawn to its interactions with another gasotransmitter, nitric oxide (NO). Here, we provide evidence that the physiological effects observed upon the application of sodium nitroprusside (SNP) and H2S can be ascribed to the generation of nitroxyl (HNO), which is a direct product of the reaction between SNP and H2S, not a consequence of released N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(151 citation statements)
references
References 59 publications
(142 reference statements)
6
141
0
Order By: Relevance
“…2B,C). These results are in accordance with the observation that the NO donor SNP prevented H2S-induced relaxation of rat uterus, an effect that was attributed to the generation of nitroxyl (HNO) [20]. Recently, it was reported that relaxation effects of neutral and anionic forms of sulfide (H2S/HS -) differ in quality and the inhibition of uterine contractility might be a consequence of the specific actions of HSin relation to its negative charge [19].…”
Section: Effects Of Sulfide Gsno Sn and The 'Ssno -Mix' On Uterus Csupporting
confidence: 90%
See 2 more Smart Citations
“…2B,C). These results are in accordance with the observation that the NO donor SNP prevented H2S-induced relaxation of rat uterus, an effect that was attributed to the generation of nitroxyl (HNO) [20]. Recently, it was reported that relaxation effects of neutral and anionic forms of sulfide (H2S/HS -) differ in quality and the inhibition of uterine contractility might be a consequence of the specific actions of HSin relation to its negative charge [19].…”
Section: Effects Of Sulfide Gsno Sn and The 'Ssno -Mix' On Uterus Csupporting
confidence: 90%
“…The mechanisms of contraction and relaxation between uterus and aorta differ. It was reported that SNP prevented H2S induced relaxation of rat uterus, and this effect was attributed to the generation of nitroxyl (HNO) [20]. From the different sensitivities of rat uterus and aorta to NO [25], it was suggested that an activation of sGC, a key mechanism for vasorelaxation in many non-uterine smooth muscle such as aortic tissue, may not be involved in uterine relaxation [35].…”
Section: Effects Of Sulfide Gsno Sn and The 'Ssno -Mix' On Aortic Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Ali and co-workers [43] demonstrated that low concentration of H2S or spontaneous H2S donors reversed histamine, but not isoprenaline-induced vasodilatation, possibly via a direct chemical reaction between H2S and NO, which may lead to the formation of a nitrosothiol [44] or even nitroxyl species (NO-/HNO) [45] of poor vasorelaxant activities.…”
Section: Discussionmentioning
confidence: 99%
“…HSNO/SNO -is reported to be further metabolized to NO + , NO, and NO -with a variety of distinct stimulatory functions, and since it can diffuse freely across membranes, it may facilitate transnitrosation of proteins (40). SNP appears to be a poor choice of an NO donor, as it directly reacts with H 2 S and produces HNO and although this is a source of HNO, the chemistry does not appear to be similar to H 2 S/NO interactions in biological systems (38). HSNO/SNO -can further react with additional H 2 S and form H 2 S 2 (40).…”
Section: Reactions With No and Related Compoundsmentioning
confidence: 99%